2021
DOI: 10.3390/nano11020273
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Chitosan in Green Synthesis of Metal Nanoparticles for Biomedical Applications

Abstract: Chitosan (CS) is a well-known stabilizer for metal nanoparticles in biomedical engineering. However, very few studies have explored other important roles of CS including reducing, shape-directing, and size-controlling. This review aims to provide the latest and most comprehensive overview of the roles of CS in the green synthesis of metal nanoparticles for biomedical applications. To the best of our knowledge, this is the first review that highlights these potentialities of CS. At first, a brief overview of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 103 publications
1
36
0
Order By: Relevance
“…Furthermore, it was possible to observe that the antimicrobial activity of functionalized surfaces increased with the decrease of CS molecular weight, as demonstrated by biofilm cell composition and structure. In fact, results point to the CS2- and CS3-PLA as the most promising surfaces in reducing the number of biofilm cells, biovolume and biofilm thickness, possibly because low Mw chitosan penetrates the bacterial cell wall more easily due to their reduced size [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was possible to observe that the antimicrobial activity of functionalized surfaces increased with the decrease of CS molecular weight, as demonstrated by biofilm cell composition and structure. In fact, results point to the CS2- and CS3-PLA as the most promising surfaces in reducing the number of biofilm cells, biovolume and biofilm thickness, possibly because low Mw chitosan penetrates the bacterial cell wall more easily due to their reduced size [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, other antimicrobial hybrid derivatives, such as nanocellulose/metal and nanocellulose/oxide metal, have attracted the attention of several researchers and industries due to their environmentally friendly status and low cost compared to synthetic polymer- (e.g., polylactic- co -glycolic acid (PLGA), polyvinylalcohol (PVA), poly(ethylene glycol) methyl ether- block -poly(lactide- co -glycolide) (mPEG-PLGA), chitosan, gelatin) encapsulated MNPs [ 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ]. Cellulose is a ubiquitous natural polymer which can be produced from a broad range of biomass.…”
Section: General Background On Antimicrobial and Anti-biofilm Metalli...mentioning
confidence: 99%
“…A variety of research groups have used them in imaging-guided PTT for in vivo cancer treatment 27 , 28 . Similarly, marine biopolymers such as chitosan (CS) have attracted considerable attention in recent years for their application in the cosmetics, nutraceutical, and pharmaceutical industries 29 , 30 . Manivasagan et al reported the combination of CS and PPy to be a strong NIR absorbance PTT agent for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%